Nível de emissão sonora em aulas de spinning e indicadores de possíveis repercussões na saúde dos profissionais que trabalham com esta atividade - Bahniuk, Paulo Henrique (2012)
Introduction: Today, noise presents itself as the most frequent physical agent in working environment and its noxiousness is proved by literature, however its effects are not limited to the hearing system. In the main consequences, it is Noise-Induced Hearing Loss (NIHL), it can be caused by any excessive kind of sound emission, including music as the ones played during aerobic gym classes, such as spinning. Objective: Analyze level of sound transmission that professionals are exposed during spinning classes and possible consequences of this agent on health. Methodology: Descriptive study that used as a research tool a dosimeter, branded Instrutherm and model Digital Portátil – DOS 500. It was used to measure the level of rustle absorbed by thirty-three spinning teachers, in Curitiba city. Furthermore, it was made an interview in order to identify the possible symptoms presented by those professionals. The average and peak of noise presented in classes were analyzed, it was also calculated the Equivalent Continuous Sound Level (LEQ) for an eight hour workload and for a specific workload in the spinning modality of these teachers. To statistical analysis it was applied the Chi-square independence test and the Fisher’s exact test. Results: The average noise level during one hour class it was of 91.25 dB(A) and the maximum value verified reached 110.6 dB(A). The LEQ for an eight hour workload reached 92.27 dB(A), however, when the LEQ was calculated in the spinning modality workload this number decreased to 82.5dB(A). It was verified that 13 people (39.4%) were exposed to a level of sound transmission higher than the maximum allowed by the Ministério do Trabalho e Emprego (MTE). About the symptoms presented, 28 of the professionals that were interviewed (84.85%) reported having some kind of complaint on the last three months. It was obtained statistical significance when the LEQ of the spinning classes and the symptomatology of the interviews (p<0,05) were correlated. The relative risk of symptoms appeared to professionals that received sound transmission above 85 dB(A) was analyzed, and it was concluded that these people have 8.62 times more chances of having such symptoms when its compared to the professionals that receive sound transmission under the quoted level. Once LEQ projected for eight hours was correlated health complaints were presented again, in other words, the level of sound transmission for an eight hour workload is related to the emerging health symptoms of the group studied. Conclusion: The sound transmission on the professional’s working environment is high, and on this subject, several of the analyzed gyms are in disagreement with the MTE legislation. Besides not being concerned with the use of individual protection equipments nor the execution of periodical and medical exams of admission in their staff, even though the participants of this research already presented indicatives of hearing injury caused by rustle and other systematic complaints which can be related to the indirect effects of this agent.